Minangkabau Women’s Politics Participation in the Tradition of Khatm Quran - Wirdanengsih, Wirdanengsih; Erianjoni, Erianjoni; Fitrisia, Azmi (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2022)
This study concerns on the women of Minangkabau in politics system that is egalitarian and has a central position within the society with the focus on the involvement of women in politics in the process and activities of Khatm Quran tradition which is a part of the local society’s responsibility. Generally, there is a representation of women in politics and local position within the local society. There is a causal relationship between women’s egalitarian characteristics and their positions in politics in daily life. In fact, egalitarian characteristics have a significant effect on the decision making process and in the process and activities of Khatm Quran tradition.